Pertambahan Bobot Badan Broiler yang diberi Bungkil Inti Sawit Hasil Fermentasi untuk Menggantikan Sebagian Ransum Komersil - Thalia Marcelina; Mairizal; Yusrizal (Jurnal Galung Tropika, 2026)
Palm kernel meal is a byproduct of the palm oil industry that possesses good nutritional potential but is limited by its high crude fiber content. Fermentation using the bacterium Bacillus cereus V9 can serve as a solution to reduce crude fiber and enhance the nutritional value of palm kernel meal, thereby potentially replacing a portion of commercial feed. This study aims to determine the optimal level of commercial feed replacement with fermented palm kernel meal (BISF) on broiler body weight gain. This study employed a completely randomized design (CRD) with 5 treatments and 4 replicates. The treatments tested were levels of commercial feed replacement with FPK, namely: P0 (100% Commercial Feed), P1 (95% Commercial Feed + 5% FPK), P2 (90% Commercial Feed + 10% BISF), P3 (85% Commercial Feed + 15% BISF), and P4 (80% Commercial Feed + 20% BISF). The parameters observed included feed intake, body weight gain, and feed conversion ratio. Data were analyzed using analysis of variance. The results showed that the use of BISF to partially replace commercial rations did not affect (P>0.05) feed consumption, body weight gain, and feed conversion in broilers. It was concluded that BISF administration up to 20% can partially replace commercial rations without affecting broiler body weight gain.